2020
DOI: 10.1136/bmjopen-2020-039041
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of the renewed National Cervical Screening Program in Australia 12 months following implementation: a qualitative study

Abstract: ObjectiveTo explore women’s experiences of the renewed National Cervical Screening Program in Australia from the perspective of women who have received different human papillomavirus (HPV) test results. Women aged 25 to 74 are now screened every 5 years with primary HPV screening.DesignQualitative interview study.SettingAustralia.ParticipantsWomen in Australia aged 25 to 74 who reported participating in cervical screening since December 2017, purposively sampled by test result (HPV positive, HPV negative and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…This is especially so for the delivery of positive HPV test results. As with the anxiety and fear associated with abnormal cervical smear test results, 24–27 positive HPV test results may cause adverse psychological and social repercussions, such as anxiety and stigmatization, especially when awareness about HPV is low 28,29 . The importance of culturally safe and empathetic care has been emphasized for Indigenous women 3,8,23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially so for the delivery of positive HPV test results. As with the anxiety and fear associated with abnormal cervical smear test results, 24–27 positive HPV test results may cause adverse psychological and social repercussions, such as anxiety and stigmatization, especially when awareness about HPV is low 28,29 . The importance of culturally safe and empathetic care has been emphasized for Indigenous women 3,8,23 …”
Section: Introductionmentioning
confidence: 99%
“…As with the anxiety and fear associated with abnormal cervical smear test results, [24][25][26][27] positive HPV test results may cause adverse psychological and social repercussions, such as anxiety and stigmatization, especially when awareness about HPV is low. 28,29 The importance of culturally safe and empathetic care has been emphasized for Indigenous women. 3,8,23 A recent community-based cluster randomized controlled trial (cRCT) in Te Tai Tokerau (Northland), 23 Aotearoa, demonstrated an almost three-fold increase in screening among Māori women when offered HPV self-testing compared to usual care, with over 80% of women who received a positive result attending their colposcopy appointment.…”
mentioning
confidence: 99%
“…Among under-screened and never-screened women, HPV self-sampling may be the preferred screening option, as supported by a randomized controlled trial reporting increase in screening uptake using this approach ( Sultana et al., 2016 , Sultana et al., 2015 ). However, no study to date has assessed the knowledge of immigrant women of the renewed program or self-sampling option ( Dodd et al., 2020 , Nagendiram et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent anxiety and psychological distress, education and counseling are increasingly important for women diagnosed with HPV. Therefore, more attention should be paid to how to communicate and provide information (18-20).…”
Section: Introductionmentioning
confidence: 99%